Inflation hedging property of housing market in Malaysia - Geok, Peng Yeap; Hooi, Hooi Lean (Universiti Sains Malaysia, 2016)
This paper aims to examine the relationship between house prices and inflation to determine the inflation hedging ability of housing in Malaysian. We examine the long-run and short-run hedging ability of house prices against both consumer and energy inflation by using ARDL approach. Consumer inflation will be calculated from consumer price index while energy inflation is calculated from crude oil price. We find that, in the long-run, housing is a good hedge against consumer inflation but a poor hedge against energy inflation. In the short-run, housing is only partially hedge against energy inflation but not able to hedge against consumer inflation. The results show that housing is not a good investment asset in Malaysia.